Relationship between frailty, social support and family functionality of hemodialysis patients: a cross-sectional study - Santos, Diana Gabriela Mendes dos; Pallone, Joice Marques; Manzini, Carlene Souza Silva; Zazzetta, Marisa Silvana; Orlandi, Fabiana de Souza (São Paulo Medical Journal, 2021)
BACKGROUND: The population with chronic kidney disease (CKD) is more predisposed to early development of frailty. Although the concept of frailty is well established from a physical point of view, it is not an exclusively physical syndrome. It can be characterized as an interaction of physical, psychological and social factors. OBJECTIVE: To ascertain the relationship between frailty, social support and family functionality among CKD patients undergoing hemodialysis. DESIGN AND SETTING: Correlational, cross-sectional and quantitative study conducted at a service in the interior of the state of São Paulo. METHODS: This study included 80 patients with CKD who were on hemodialysis. The participants were interviewed individually, with application of the following instruments: sociodemographic and economic characterization, Tilburg Frailty Indicator, Medical Outcomes Study and Family APGAR. Females and white ethnicity predominated among the participants, and their mean age was 59.63 ± 15.14 years. RESULTS: There was high prevalence of frailty (93.8%). Although there was a difference in scores for the dimensions of social support between the frail group and the non-frail group, only family functionality reached a statistically relevant difference. There was a significant correlation between physical frailty, social support and family functionality. CONCLUSIONS: Presence of frailty is related to the social support and family functionality of patients with CKD undergoing hemodialysis.